Education and socialization of the 'Love Your Breast' mobile application: A strategy for early detection of breast cancer in young women - Anggraini, Dian; Listiana, Nurzalillah (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2024)
Breast cancer ranks among the primary causes of mortality in women. A technique for identifying early indicators of breast cancer is Breast Self-Examination (BSE). BSE is a readily available and efficient method for early detection. The awareness of women regarding early breast cancer screening profoundly influences their health views and attitudes. The absence of sensitivity, curiosity, and proactivity among young women in pursuing information on BSE has resulted in insufficient understanding of early detection methods. The socialization of mobile applications can significantly aid by offering accessible information on BSE and reminders for the ideal occasions to perform self-examinations. This method can enhance understanding and awareness of breast cancer. This program seeks to inform and advocate for the "Love Your Breast" mobile application as a resource for early breast cancer diagnosis in young women. The implementation has three phases: preparation, execution, and monitoring and assessment. The findings reveal a substantial enhancement in knowledge scores post-education (p-value < 0.05), illustrating the efficacy of this method.